1996
DOI: 10.1097/00043764-199612000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Isocyanates and Organic Solvents, and Pulmonary-Function Changes in Workers in a Polyurethane Molding Process

Abstract: The extent of adverse health effects of isocyanates when combined with other chemicals is not well documented. This study was conducted as a 2.5-year follow-up as well as to determine daily and weekly effects of exposure to isocyanates and organic solvents on pulmonary function. The concentrations of chemicals sampled were below the recommended exposure criteria. No daily or weekly reduction in the subjects' pulmonary function was observed. The isocyanate/solvent-exposed subjects showed significant long-term r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In line to ours, above studies demonstrated that chronic exposure to solvents may cause adverse effects on respiratory system. In contrast, Akbar-Khanzadeh and Rivas 23 showed that no significant difference was in proportion of respiratory symptoms between the solvent-exposed group and non-exposed group in polyurethane molding process workers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In line to ours, above studies demonstrated that chronic exposure to solvents may cause adverse effects on respiratory system. In contrast, Akbar-Khanzadeh and Rivas 23 showed that no significant difference was in proportion of respiratory symptoms between the solvent-exposed group and non-exposed group in polyurethane molding process workers.…”
Section: Discussionmentioning
confidence: 84%
“…18 The difference in pulmonary function was not observed between non-exposed subjects and those exposed only to organic solvents in workers in a polyurethane molding process. 23 In contrast, the measured ventilatory capacity values in exposed workers to solvents were significantly lower in comparison to control in shoe manufacturing workers. 19 Provided that we had evaluated the atopy and bronchial hyper-responsiveness in workers and measured the concentrations of the chemical irritants in the environment would be better for an improved assessment.…”
Section: Article In Pressmentioning
confidence: 84%
“…There was a notable background prevalence of work related symptoms in the no spray no heat group—21% of women and 18% of men—possibly due to intermittent exposure to isocyanates in combination with dusts21 and solvents 37. Interestingly, in the air measurements from 1993, relatively high concentrations of MDI (up to 7.1 μg/l) were found in the no spray no heat group, indicating a widespread contamination of the workplace 10…”
Section: Discussionmentioning
confidence: 96%
“…Cumulative exposure in plastic molding was associated with sore eyes and tingling of limbs. Workers in this task could be exposed to diisocyanates, a strong irritant compound that produces eye and airway in¯ammation [Akbar-Khanzadeh and Rivas, 1996], and to different solvents such as n-hexane that are responsible for toxic polyneuropathy [Giuliano et al, 1975]. The pyrolysis products of heated polyvinyl chloride (PVC), e.g., hydrochloric acid could also produce airway in¯ammation [Ng et al, 1991;Oleru and Onyekwere, 1992].…”
Section: Discussionmentioning
confidence: 99%